2022
DOI: 10.1038/s12276-022-00896-9
|View full text |Cite
|
Sign up to set email alerts
|

Delineating the dynamic evolution from preneoplasia to invasive lung adenocarcinoma by integrating single-cell RNA sequencing and spatial transcriptomics

Abstract: The cell ecology and spatial niche implicated in the dynamic and sequential process of lung adenocarcinoma (LUAD) from adenocarcinoma in situ (AIS) to minimally invasive adenocarcinoma (MIA) and subsequent invasive adenocarcinoma (IAC) have not yet been elucidated. Here, we performed an integrative analysis of single-cell RNA sequencing (scRNA-seq) and spatial transcriptomics (ST) to characterize the cell atlas of the invasion trajectory of LUAD. We found that the UBE2C + cancer cell subpopulation constantly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 72 publications
2
40
0
Order By: Relevance
“…The proportion of SPP1 + TAM cells was higher in IA compared to N, but not greater in MIA than N. In contrast, the proportion of CTSB + TAM cells in both IA and MIA were significantly higher than that in N, suggesting that CTSB + TAM cells, instead of SPP1 + TAM cells, play a crucial role in MIA (Figure 5I). Consistent with these results, we found that the expression of CTSB was higher in the cells from MIA samples compared to that from IA sample in GSE189487 datasets [14] (Figure 5J), while the expression of SPP1 was lower in the cells from MIA samples compared to that from IA samples (Figure 5K). An integrated dataset of 719 LUAD patients corrected by Gyorffy [20] showed that high expression levels of both CTSB and SPP1 significantly was associated with poor survival, highlighting the critical role of CTSB + and SPP1 + TAM in the progression of LUAD (Figure 5L,M).…”
Section: Cathepsin B (Ctsb)+ Tumor-associated Macrophages (Tams) As T...supporting
confidence: 84%
See 1 more Smart Citation
“…The proportion of SPP1 + TAM cells was higher in IA compared to N, but not greater in MIA than N. In contrast, the proportion of CTSB + TAM cells in both IA and MIA were significantly higher than that in N, suggesting that CTSB + TAM cells, instead of SPP1 + TAM cells, play a crucial role in MIA (Figure 5I). Consistent with these results, we found that the expression of CTSB was higher in the cells from MIA samples compared to that from IA sample in GSE189487 datasets [14] (Figure 5J), while the expression of SPP1 was lower in the cells from MIA samples compared to that from IA samples (Figure 5K). An integrated dataset of 719 LUAD patients corrected by Gyorffy [20] showed that high expression levels of both CTSB and SPP1 significantly was associated with poor survival, highlighting the critical role of CTSB + and SPP1 + TAM in the progression of LUAD (Figure 5L,M).…”
Section: Cathepsin B (Ctsb)+ Tumor-associated Macrophages (Tams) As T...supporting
confidence: 84%
“…The number and function of CD8 + T cells in LUAD decline with disease progression, but their status in MIA remains controversial. [12][13][14][15]27] Here, we showed that MIA has a similar immune infiltration environment to normal tissue, but both the quantity and quality of CD8 + T cells decrease from MIA to IA. The anti-tumor microenvironment of MIA may help restrain tumor growth and confer its indolent nature.…”
Section: Discussionmentioning
confidence: 88%
“…[28,29] What more, some researchers found that the subpopulation of cancer cells expressing UBE2C increased during the invasion of lung adenocarcinoma cells into normal tissues, distributed in the periphery of cancerous tissues, and possessed strong invasiveness. [30] And the expression level of UBE2C gradually increases as the degree of tumor differentiation decreases. [31] The emergence of drug resistance during the treatment of tumors often indicates a poorer prognosis for patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 90 ] Increased Tregs and decreased monocytes have been shown to activate tumor‐associated pathways, thereby promoting early LUAD invasion. [ 74 ] Liver is the most important target organ for CRC metastasis, and colorectal cancer liver metastasis (CRLM) has a highly heterogeneous and suppressive immune microenvironment, which is one of the bottlenecks and difficulties for CRC treatment. By scRNA‐seq and SRT sequencing of paired samples of CRC and liver metastasis, Wu et al.…”
Section: Applications Of Srt Technology In Cancer Researchmentioning
confidence: 99%